Тhe importance of self-control, and education of patients with diabetes mellitus type 2 in the prevention of micro and macrovascular complications - Sandra Živanović; Viktorija Artinović; Nevena Vasović (Mенаџмент у хотелијерству и туризму, 2013)
Diabetes mellitus belongs to a group of metabolic disorders which share a common phenotype of hyperglycemia. Aging significantly increases the prevalence of diabetes , namely according to the Framingham study, 10-15% people over the age of 60 have diabetes, in whose pathogenesis the resistance of tissues to insulin is dominant. According to the theoretical model, diabetes is a kind of accelerated aging. The close connection between the obesity epidemic and the development of insulin resistance and type 2 diabetes have shown the key role that obesity has in the pathogenesis of these two disorders. Among the risk factors that are the most responsible for the overall mortality rate in the world, factor of the physical inactivity has a high position. Hyperglycemia of patients with diabetes increases the activity of aldose reductase, the enzyme that converts glucose into sorbitol is associated with oxidative stress and damage of nerves. Dyck and his collaborators believe that sooner or later all patients with diabetes will get some type of diabetic neuropathy. Self - control, education and team work of professionals are essential in the prevention of acute and chronic complications among patients. The degree of self - control of patients with diabetes in Serbia and Europe differs significantly. Work on education of patients and early non - invasive diagnosis, which includes screening of those organs and organ systems that are predilection sites for development of complications characteristic for this type of disease.